Artificial Intelligence and Economic Productivity: A Comparative Assessment of Algeria’s Readiness and Development Prospects - ZIANE, Lakhdar; BOUKRIF, Moussa (Journal of Ecohumanism, 2026)
Artificial intelligence (AI) is rapidly transforming global economies by enhancing productivity, enabling innovation, and reshaping labor markets. While advanced economies have integrated AI technologies at scale, emerging economies such as Algeria face structural and institutional challenges that limit the potential impact of AI on productivity growth (Agrawal, Gans, & Goldfarb, 2019; Acemoglu & Restrepo, 2020). This study provides a comparative assessment of Algeria’s readiness to adopt AI for economic productivity, benchmarking its performance against Morocco, Egypt, and Turkey. Using data from the World Bank (2022), Oxford Insights Government AI Readiness Index, and sector-specific studies, the analysis identifies strengths, gaps, and opportunities for AI-driven economic transformation. Findings reveal that Algeria exhibits significant lag in digital infrastructure, human capital, and institutional frameworks compared to peers, yet targeted investments and policy reforms could accelerate AI adoption and productivity gains (Brynjolfsson, Rock, and Syverson, 2017; McKinsey & Company, 2023). The paper concludes with policy recommendations to foster a conducive environment for AI integration, positioning Algeria to leverage technological advances for sustainable economic growth.